Family background and school performance: an approach with binary variables from SARESP results - Bassetto, Camila Fernanda [UNESP] (Associacao Brasileira de Estudos Populacionais, 2019)
This study researches the impact of outside school factors on individuals’ schooling. Income and maternal schooling are taken into consideration when measuring the effect of familiar aspects on students’ performance in Mathematics. Therefore, we used data referring to the Mathematics grade of students in 3rd year High School, and the answers provided by their parents for the socioeconomic questionnaire, applied by SARESP in its 2013 edition. Models with binary variables are proposed and estimates for parameters are obtained with SPSS. Results show that students from families with higher incomes indicate better educational performance, but there are restrictions. The level of maternal education positively influences student’s performance, but is limited to appropriate proficiency levels.
Fondo familiar y desempeño escolar: Un enfoque con variables binarias a partir de los resultados del SARESP
Background familiar e desempenho escolar: Uma abordagem com variáveis binárias a partir dos resultados do SARESP
Keywords: Binary variables; Family income; Maternal education; Proficiency in mathematics; SARESP